Space division multiple access for wireless local area networks - Vandenameele, Patrick (Kluwer international series in engineering and computer science, 2002)
The tendency towards more mobility and flexibility favors wireless networks for future broadband services, especially in local area and residential networks. Two major challenges in developing such high data-rate wireless networks are the channel distortion caused by multipath propagation and the limitations on bandwidth usage. In this book, novel transmission techniques are proposed that achieve multi-path mitigation, through orthogonal frequency-domain processing, in combination with a high bandwidth efficiency, through space division multiple access (SDMA). By exploiting the parallelism in the data-model and the frequency-selectivity of the propagation channel, high-performance non-linear detection algorithms with modest complexity requirements are obtained. In addition to discussing these core detection algorithms, this book pays special attention to the real-world problems encountered when integrating these into a complete system. Most notably, an optimal multi-user channel estimator and a combined pre- and post-synchronization approach are presented. Furthermore, complexity reduction is a recurring theme throughout the book. It has been addressed on several levels in the system design and encompasses network architecture, algorithmic and implementation architecture optimizations. Finally, an extended version of the recently finalized HIPERLAN-II standard is presented, which demonstrates the applicability of the proposed techniques and assesses their joint performance. Space Division Multiple Access for Wireless Local Area Networks is appropriate for practitioners and researchers in the mobile communications and wireless fields.